THE MAIL INFORMATION SYSTEM DESIGN WEBSITE BASED BY USING THE INTERNET NETWORK IN INDONESIAN NAVAL TECHNOLOGY COLLEGE ENVIRONMENT - Syahlan, Zainal; Nur Azis, Muhammad (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2024)
Secretariat section or Indonesian Naval Technology College Secretariat Section is a work unit under Setlem as the secretary of the institution in charge of administering administrative services in the form of correspondence. Good incoming mail management procedures include; grouping of letters, checking of mail, recording of lmail and distributing mails as well as filing of mails, while for outgoing mail include; drafting mails, mail draft approval, letter typing, numbering, lmail preparation, mail delivery. At this time the mail processing process is still done manually so that it affects the decision making quickly and accurately and minimizes errors. To build a service unit that is integrated and capable of providing excellent service quality, it is necessary to have a management that encourages efficiency and accelerates the process of implementing service tasks and functions. The management includes the Standard Operation System (SOP) and the implementation of E-Office for the implementation of the duties and functions of the service unit as well as the documentation or archive system. With the website-based mail information system in the Indonesian Naval Technology College environment, all forms of mail, both incoming and outgoing letters, will be carried out electronically, which is integrated from the Commander to the Work unit Work unit below. From the results of this study, the ease of processing letters can help in making decisions accurately and quickly. Keywords: E-Office, Indonesian Naval Technology College Secretariat section, Information System, mail.